Electronic band structure and optical properties of titanium oxyphosphates Li0.50Co0.25TiO(PO4) single crystals: An ab-initio calculations - Ali Hussain, Reshak, Prof. Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Kityk, I. V.; Khenata, R.; Auluck, S. (Elsevier Inc., 2011)
Link to publisher's homepage at http://www.elsevier.com/